Production Of Chitinase By Streptomyces Hygroscopicus VMCH2 By Optimisation Of Cultural Conditions - PRIYA.C.S; JAGANNATHAN.N; KALAICHELVAN.P.T (International Journal of Pharma and Bio Sciences, 2011)
A total of 10 chitinolytic bacteria were isolated from 35 soil samples collected from different crop fields in Tamilnadu state, India. Among them, a strain designated as VMCH2 which produced highest chitinolytic activity in primary and secondary screening in colloidal chitin agar was selected and later identified as Sterptomyces hygroscopicus. The maximum chitinase production was observed in CCMB amended with 0.2% colloidal chitin at pH 7.0 and 35° C after 8 days of incubation. Under this optimized growth conditions, Streptomyces hygroscopicus - VMCH2 produced a total chitinase activity of 28. 09 units / ml against only 9.36 units / ml in the initial production medium stage.